2015
DOI: 10.1002/cncr.29452
|View full text |Cite
|
Sign up to set email alerts
|

Both tumor depth and diameter are predictive of sentinel lymph node status and survival in Merkel cell carcinoma

Abstract: BACKGROUND The purposes of this study were 1) to determine the impact of primary tumor-related factors on the prediction of the sentinel lymph node (SLN) status and 2) to identify clinical and pathologic factors associated with survival in Merkel cell carcinoma (MCC). METHODS An institutional review board–approved, retrospective review of patients with MCC treated between 1988 and 2011 at a single center was performed. Patients were categorized into 5 groups: 1) negative SLN, 2) positive SLN, 3) clinically n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 30 publications
5
61
0
6
Order By: Relevance
“…At the time of initial diagnosis, up to 20 % of patients present with clinically manifest lymphogenic metastases and thus have a poor prognosis . In addition, almost one‐third of the patients have lymphogenic, clinically inapparent micrometastases . It is therefore imperative that patients be worked up for locoregional spread at the time of initial diagnosis, either by lymph node ultrasound of the draining lymph node basins and/or cross‐sectional imaging.…”
Section: Diagnosismentioning
confidence: 99%
“…At the time of initial diagnosis, up to 20 % of patients present with clinically manifest lymphogenic metastases and thus have a poor prognosis . In addition, almost one‐third of the patients have lymphogenic, clinically inapparent micrometastases . It is therefore imperative that patients be worked up for locoregional spread at the time of initial diagnosis, either by lymph node ultrasound of the draining lymph node basins and/or cross‐sectional imaging.…”
Section: Diagnosismentioning
confidence: 99%
“…Fields et al reported that MCC size and LVI were correlated with SLN status, whereas Schwartz et al showed that MCC thickness, mitotic rate, and histologic growth pattern significantly predicted SLN status in a multivariate analysis. Smith et al also report that MCC size and thickness significantly predict SLN status in a univariate analysis, and their results provide more evidence that these factors are prognostic markers for SLN status. Interestingly, 1 study looked at the Veterans Affairs national health care database and reported that MCC patients with tumors ≤ 1 cm in size may not benefit from nodal staging .…”
mentioning
confidence: 92%
“…Instead, Smith et al evaluated the prognostic significance of tumor thickness in MCC. Although MCC size has been correlated with survival, the prognostic value of tumor thickness remains undefined.…”
mentioning
confidence: 99%
See 2 more Smart Citations